The IoRT-in-Hand: Tele-Robotic Echography and Digital Twins on Mobile Devices. - Bravo-Arrabal, Juan; Cheng, Zhuoqi; Fernández-Lozano, Juan Jesús; Gómez-Ruiz, José Antonio; Schlette, Christian; Savarimuthu, Thisius Rajeeth; Mandow, Anthony; García-Cerezo, Alfonso José (MDPI, 2025)
The integration of robotics and mobile networks (5G/6G) through the Internet of Robotic Things (IoRT) is revolutionizing telemedicine, enabling remote physician participation in scenarios where specialists are scarce, where there is a high risk to them, such as in conflicts or natural disasters, or where access to a medical facility is not possible. Nevertheless, touching a human safely with a robotic arm in non-engineered or even out-of-hospital environments presents substantial challenges. This article presents a novel IoRT approach for healthcare in or from remote areas, enabling interaction between a specialist’s hand and a robotic hand. We introduce the IoRT-in-hand: a smart, lightweight end-effector that extends the specialist’s hand, integrating a medical instrument, an RGB camera with servos, a force/torque sensor, and a mini-PC with Internet connectivity. Additionally, we propose an open-source Android app combining MQTT and ROS for real-time remote manipulation, alongside an Edge–Cloud architecture that links the physical robot with its Digital Twin (DT), enabling precise control and 3D visual feedback of the robot’s environment. A proof of concept is presented for the proposed tele-robotic system, using a 6-DOF manipulator with the IoRT-in-hand to perform an ultrasound scan. Teleoperation was conducted over 2300 km via a 5G NSA network on the operator side and a wired network in a laboratory on the robot side. Performance was assessed through human subject feedback, sensory data, and latency measurements, demonstrating the system’s potential for remote healthcare and emergency applications. The source code and CAD models of the IoRT-in-hand prototype are publicly available in an open-access repository to encourage reproducibility and facilitate further developments in robotic telemedicine.
Keywords: Informática en la nube; Internet de los objetos; Robótica; Medicina - Material y equipo; Ingeniería biomédica; Simulación por ordenador; Android; Cloud robotics; Digital Twins; Medical instruments; Tele-operation